2002
DOI: 10.1023/a:1020631932528
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effect of 5-hydroxytryptamine (serotonin) on neuromuscular transmission in frog skeletal muscle was studied using voltage clamp technique. Serotonin produced no effect on end-plate currents during low frequency electrical stimulation of the motor nerve, but increased the amplitude depression of multiquantal currents during high-frequency stimulation similar to motor commands fired by motoneurons. It was shown that the inhibitory effect of serotonin on neuromuscular transmission is determined by slow potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Hill's constant was practically the same as for neuronal cholinoreceptors ( n H = 1.1 [6]), which indicated that the channel was blocked by a single molecule of the blocking agent, whereas the concentration at which the blocking-agent effect was half the maximum ( I C 50 ) for muscle cholinoreceptors was considerably higher than that for neuronal receptors (0.34 µ M [6]). The latter suggests that mecamilamine has a smaller blocking effect on muscle cholinoreceptors.With respect to its EEC time-amplitude characteristics, mecamilamine is analogous to a desensitization promoter or a slow blocking agent of open channels, whose characteristic property is the enhancement of the inhibiting effect upon increasing the frequency of nerve stimulation [10][11][12]. However, our experiments with mecamilamine showed that the increase in the frequency of nerve stimulation to 10 Hz did not induce additional changes in current amplitudes, which indicates another action mechanism of this compound.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Hill's constant was practically the same as for neuronal cholinoreceptors ( n H = 1.1 [6]), which indicated that the channel was blocked by a single molecule of the blocking agent, whereas the concentration at which the blocking-agent effect was half the maximum ( I C 50 ) for muscle cholinoreceptors was considerably higher than that for neuronal receptors (0.34 µ M [6]). The latter suggests that mecamilamine has a smaller blocking effect on muscle cholinoreceptors.With respect to its EEC time-amplitude characteristics, mecamilamine is analogous to a desensitization promoter or a slow blocking agent of open channels, whose characteristic property is the enhancement of the inhibiting effect upon increasing the frequency of nerve stimulation [10][11][12]. However, our experiments with mecamilamine showed that the increase in the frequency of nerve stimulation to 10 Hz did not induce additional changes in current amplitudes, which indicates another action mechanism of this compound.…”
mentioning
confidence: 66%
“…With respect to its EEC time-amplitude characteristics, mecamilamine is analogous to a desensitization promoter or a slow blocking agent of open channels, whose characteristic property is the enhancement of the inhibiting effect upon increasing the frequency of nerve stimulation [10][11][12]. However, our experiments with mecamilamine showed that the increase in the frequency of nerve stimulation to 10 Hz did not induce additional changes in current amplitudes, which indicates another action mechanism of this compound.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…It has been previously suggested that chlorhexidine has a channel-blocking effect on a neuromuscular junction [1], although the type and mechanisms of this blockage remain unclear. Therefore, in this study, we analyzed the mechanism underlying the chlorhexidine effect on the receptor-channel complex of the muscle cholinoreceptor.Isolated neuromuscular preparations (sciatic nervetailor's muscle) were obtained from frogs by a previously described standard two-electrode voltage clamp procedure [2]. Under rare electric stimulation (0.05 Hz), chlorhexidine at concentrations of 2-15 µ M caused a concentration-dependent decrease in the amplitude and the time constant of the decline of evoked postsynaptic currents (EPCs).…”
mentioning
confidence: 99%
“…Isolated neuromuscular preparations (sciatic nervetailor's muscle) were obtained from frogs by a previously described standard two-electrode voltage clamp procedure [2]. Under rare electric stimulation (0.05 Hz), chlorhexidine at concentrations of 2-15 µ M caused a concentration-dependent decrease in the amplitude and the time constant of the decline of evoked postsynaptic currents (EPCs).…”
mentioning
confidence: 99%